Preliminary Study on Morphological anh Genetic Characteristics of some Native Honeybee (apis cerana) Populations in Northern Vietnam - Nguyen Van Niem, Le Quang Trung, Pham Hong Thai, Trinh Dinh Dat, Nguyen Thi Minh Nguyet, Tran Thi Ton Hoai (H. : ĐHQGHN, 2017)
tr. 24-31